Identifikasi Potensi Longsor di Kecamatan Baturiti Tabanan Bali - I NENGAH KARIASA; I NYOMAN PUJA; TATIEK KUSMAWATI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
Identification of landslide potential in Baturiti District Tabanan Bali Districts Baturiti has most areas with a slope above 15%, land use as seasonal crop farming and rainfall is high enough to potentially the occurrence of landslide hazard. Based on the above, it is necessary to conduct research on potential landslide with the aim to know the level of landslide potential and map the potential spread of landslides in Districts Baturiti. This research was conducted from February to August 2017 with survey and scoring method. The study area has 12 units of land covering the low landslide potential class of 61764.2 hectares (77.1%). is present in the area represented by the land units 1,2,5,6 and 9. The medium landslide potential class of 9415,8 ha (11,7%) is in area which is represented by unit of land 3,7,10. The high landslide potential class of 8959.4 ha (11.2%) is in the area represented by the land unit 4,8,11,12.